nvestigating Generic Structure of English Research Articles: Writing Strategy Differences between English and Indonesian Writers - Ni Ketut Mirahayuni (TEFLIN, 2003)
Research into English research articles (RAs) has largely been focused on articles produced by native English writers. This paper reports a study aiming to investigate the textual structure of research articles written by non-native English (i.e. Indonesian) writers, which may contribute to their acceptance for international publication. A comparison is made between RAs written by native English speakers, an Indonesian writers writing in English, all in the field of Language and Language Teaching. It explores the relation of texts generic structure. The thesis develops a framework for the generic structure analysis based on Swales (1990) Create-A-Research-Space (CARS) model of moves. The analysis focuses on two RA sections: Introduction and Discussion. The findings indicate significant differences in both forms and functions of organizing strategies between the native and non-native texts. The differences may partly be due to the influence of writing practices in the non-native writers first language and partly to the writers attempt to find an appropriate format in the absence of well-established research writing conventions in the first language. Consequently, non-native English texts may show organizing strategies unfamiliar to both the native English and native Indonesian texts. Findings from the research highlight two issues. First, formal and functional differences of generic structure elements and their realizations between the native and non-native English texts may disadvantage the non-native writers, particularly with regards to employment of unfamiliar organizational strategies. Second, non-native English writers need to acquire knowledge of commonly used formal generic structure, and more importantly, the knowledge of the nature of scientific writing in English to be able to gain wider readership. The implications for further research and the teaching of academic writing are discussed.